University living labs: tools for green transition and sustainable development - Góral, Anna; Wrona, Sylwia; Jałocha, Beata; Jedynak, Monika (Journal of Management and Financial Sciences, 2025)
This study delves into the potential of living labs (LLs) as transformative tools for sustainability and green transition within university settings. Through a scoping review analyzing 38 scholarly articles, the research addresses the central question: How can living labs be a tool for transforming universities in the field of sustainability? The analysis reveals that universities frequently use living labs comprehensively in all three dimensions of sustainability. Living labs are identified as multifaceted entities, serving as research methods, stakeholder collaboration platforms, educational tools, and institutional frameworks. Additionally, the research underscores the significant role of living labs across various domains of university management. The findings suggest that living labs may play pivotal roles in nurturing sustainable practices within academic institutions. This study contributes to the understanding of the dynamic interplay between living labs and sustainability initiatives in higher education contexts.